The calculation of the charge density distributions of the 1f-2p shell nuclei using the occupation numbers of the states - Abdullah , Ahmed N. (Iraqi Journal of Science, 2022)
The charge density distributions (CDD) and the elastic electron scattering form factors, F(q), of the ground state for some 1f-2p shell nuclei, such as 74Ge, 76Ge, 78Se and 80Se nuclei have been calculated based on the use of occupation numbers of the states and the single particle wave functions of the harmonic oscillator potential with size parameters chosen to reproduce the observed root mean square charge radii for all considered nuclei. It is found that introducing additional parameters, namely β1 and β2 which reflect the difference of the occupation numbers of the states from the prediction of the simple shell model leads to a remarkable agreement between the calculated and experimental results of the charge density distributions throughout the whole range of r. The calculated elastic electron scattering form factors from 74Ge, 76Ge, 78Se and 80Se nuclei are very good agreement with the fitted to the experimental data throughout all values of q.